2018
DOI: 10.1016/j.jval.2018.09.141
|View full text |Cite
|
Sign up to set email alerts
|

Pcn59 - Association Between Hazard Ratios of Surrogate Time-to-Event Endpoints and Overall Survival in Advanced/Metastatic Cancers

Abstract: OBJECTIVES: Surrogate endpoints can support early access to novel therapies. In trial-level endpoint validation studies, the association between treatment effect e.g., the hazard ratio (HR) on both the surrogate and hard endpoint can be estimated. We aimed to review studies reporting an association between HRs of surrogate time-to-event endpoints and overall survival (OS) in advanced/metastatic cancers. METHODS: A systematic review was conducted using Medline and Embase. We included full reports assessing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“… 11 These recommendations require confidence intervals and STE to validate the surrogacy. Consistent with previous studies, 23 , 29 we found these items poorly reported. Because of the different recommendations, authors have difficulty choosing the right method to assess surrogacy.…”
Section: Discussionsupporting
confidence: 92%
“… 11 These recommendations require confidence intervals and STE to validate the surrogacy. Consistent with previous studies, 23 , 29 we found these items poorly reported. Because of the different recommendations, authors have difficulty choosing the right method to assess surrogacy.…”
Section: Discussionsupporting
confidence: 92%